Designing a Pedestrian Crossing Aid Prototype Based on Arduino Mega - Anando Vilgadiandra Suherman, Tri (Jurnal Indonesia Sosial Sains, 2026)
Pedestrian safety at road crossings is a critical global challenge, with the World Health Organization reporting that pedestrians account for 23% of all road traffic deaths worldwide. In rapidly urbanizing areas like Cibubur, East Jakarta, inadequate crossing facilities heighten risks amid intensifying traffic on the Cibubur Alternative Highway. Systematic observations over three days (December 15–17, 2022) revealed peak-hour traffic volumes of 2,860 vehicles and a 32.9% drop in pedestrian crossings due to safety fears. This study designs, develops, and tests an Arduino Mega-based pedestrian crossing aid prototype that uses HC-SR04 ultrasonic sensors to detect pedestrians automatically and control traffic lights without manual buttons. The three-stage architecture includes input processing via distance measurement, Arduino Mega logic for decisions, and LED outputs for signals. Testing confirmed 100% accuracy in detecting objects within 10 inches (25.4 cm) and activating red lights over 50 iterations. This low-cost ($30 USD/unit), open-source solution advances embedded systems for pedestrian safety, offering adaptable traffic management in resource-limited urban areas lacking conventional infrastructure.